Influenza Vaccination Behaviour of Healthcare Workers in Switzerland: A Cross-Sectional Study - Phung Lang; Charlotte Tsu-Shin Wu; Anna Florence Le-Nguyen; Astrid Czock (Frontiers Media S.A., 2023)
Objectives: As no data are available regarding the influenza vaccination status of Swiss healthcare workers (HCW) in the ambulatory setting, this study aims to investigate their influenza vaccination behaviours.Methods: We conducted an online survey using a four-item, semi-structured questionnaire to assess HCWs influenza vaccination coverage and behaviour. Associations between influenza vaccination status, age and language as well as recommendation behaviour and reasons for vaccination were assessed using descriptive statistics and logistic regression analyses.Results: Of the 1057 completed questionnaires, 425 (40.2%) HCW were vaccinated and 632 (59.8%) not. 78.1% of the physicians and 47.3% pharmacists were vaccinated, compared to only 29.1% of the nurses, 24.3% pharmacy technicians and 13.0% medical practice assistants (MPA). There was a significant association between influenza vaccination status and HCW profession, age, language and how often an influenza vaccination recommendation was made.Conclusion: Demographic factors seem to influence HCWs' attitudes towards influenza vaccination, which in turn affects the prospect of them recommending the influenza vaccination. Diverse strategies might be necessary to encourage HCW to get vaccinated and hence, promote influenza vaccination.